Single-pond system for integration of polluted water reclamation with tilapia fingerling production - Phan, Van Minh (Gent University, 2006)
The increase in population, the rapid economic development and an uncontrolled urbanization without sufficient environmental infrastructures have led to a severe pollution of surface waters in Ho Chi Minh city, South of Vietnam. The most obvuous and immediate damage caused by this water pollution is the shortage of an adequate water supply source for farming systems in peri-urban areas